2010
DOI: 10.1136/emj.2009.088831
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrest in infancy: don't forget glucose!

Abstract: A 2-year-old girl was brought to the Emergency Department having collapsed at home. She was unconscious and apnoeic with a sinus bradycardia of 50 beats/min. Cardiopulonary resuscitation (CPR) was commenced and her airway was secured. Epinephrine and atropine were administered. The blood glucose was found to be <0.5 mmol/l. There were minimal ketones found in both urine and serum. A bolus of 5 ml/kg of 10% dextrose was administered. Following a third cycle of CPR, a strong pulse was palpated with a sinus tachy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Do not give glucose-containing fluids during CPR unless hypoglycaemia is present. 604 Avoid hyper-and hypoglycaemia following ROSC. 605 Magnesium.…”
Section: Circulationmentioning
confidence: 99%
“…Do not give glucose-containing fluids during CPR unless hypoglycaemia is present. 604 Avoid hyper-and hypoglycaemia following ROSC. 605 Magnesium.…”
Section: Circulationmentioning
confidence: 99%
“…Fatty acid oxidation defect can result in acute metabolic episodes or sudden death. 40 42 These findings indicate that metabolic crisis, such as inhibition of fatty acid metabolism and alteration of glucose levels, may develop various clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…She had severe hypoketotic hypoglycaemia and was subsequently confirmed MCADD 5. Liang et al 6 published the first case of genetically confirmed MCADD in China, a case of a 2-year-old girl who presented with hepatomegaly and abnormal liver function following a common illness having been a previously well child.…”
Section: Discussionmentioning
confidence: 99%
“…Salter et al 5 published a case in Ireland of a 2-year-old girl presenting to the emergency room unconscious and in cardiac arrest. She had severe hypoketotic hypoglycaemia and was subsequently confirmed MCADD 5.…”
Section: Discussionmentioning
confidence: 99%